2013
DOI: 10.2214/ajr.12.10390
|View full text |Cite
|
Sign up to set email alerts
|

Screening Mammography for Women in Their 40s: A Retrospective Study of the Potential Impact of the U.S. Preventive Service Task Force's 2009 Breast Cancer Screening Recommendations

Abstract: From 2007 through 2010, patients in their 40s accounted for one third of the population undergoing screening mammography and for nearly 20% of the screening-detected breast cancers--more than half of which were invasive. This information should be a useful contribution to counseling women in this age group when discussing whether or not to pursue regular screening mammography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
4

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
4
0
4
Order By: Relevance
“…Similar to our results, 65% of their patients had invasive disease, and 15% had axillary metastases [41]. In 2013, Arleo et al [42] found that 92% of their 40-to 49-year-old screen-detected cancer patients lacked first-degree family history and that 74% lacked extremely dense breast tissue. In 1995, Curpen et al [43] found that 81% of 40-to 49-year-old women with screendetected cancer lacked family history.…”
Section: Price Et Alsupporting
confidence: 87%
“…Similar to our results, 65% of their patients had invasive disease, and 15% had axillary metastases [41]. In 2013, Arleo et al [42] found that 92% of their 40-to 49-year-old screen-detected cancer patients lacked first-degree family history and that 74% lacked extremely dense breast tissue. In 1995, Curpen et al [43] found that 81% of 40-to 49-year-old women with screendetected cancer lacked family history.…”
Section: Price Et Alsupporting
confidence: 87%
“…Accordingly, the delay of screening in this age group leads to the finding of more and larger later-stage tumours. 37,38,39…”
Section: Screening Mammography In the 40–50 Years Age Groupmentioning
confidence: 99%
“…Single-view mammography was not good enough in the early days of screening to detect tumours in young, dense breasts. 38…”
Section: Screening Mammography In the 40–50 Years Age Groupmentioning
confidence: 99%
“…Studies continued to add to the preexisting literature that supported annual mammography as the optimal approach for maximum benefit [2,5,6]. Other studies highlighted the critical importance of screening women 40-49 years old annually because of a shorter sojourn time, resulting in improved survival and decreased breast cancer treatment-related morbidity [6][7][8][9][10][11][12][13].…”
Section: Screening Mammography Practices Of Breast Imagersmentioning
confidence: 99%